A new genus of schizomids (Arachnida: Schizomida: Hubbardiidae) from Mexico, with notes on its systematics. Issue 5 (3rd September 2017) - Monjaraz-Ruedas, Rodrigo; Francke, Oscar F.
Abstract : During the systematic revision of Mayazomus, the third most diverse genus of micro whip-scorpions in North America, we found three species with peculiar morphological variation, which are different from those diagnostic characters for Mayazomus . These species share with Mayazomus the large body size and the unusual development of the male pedipalps; however, these three species share the shape of the female spermathecae with Stenochrus rather than with Mayazomus. Therefore, their phylogenetic placements create a dilemma. Here we perform analyses with morphological evidence, using two different methodologies (Parsimony and Bayesian inference) in order to hypothesize the phylogenetic relationships of the three species mentioned with each other and with respect to other North American and/or Central American genera. The results confirm our initial hypothesis that the species belong to a different genus, Olmeca gen. nov., which is recovered as the sister group of all hubbardiine genera included in these analyses, except for the genus Hubbardia . The results also indicate that despite sharing some morphological similarities, it is distantly related with Mayazomus . Three species are described herein: Olmeca brujo sp. nov., Olmeca cruzlopezi sp. nov., and Olmeca santibanezi sp. nov. Additionally, we provide a hypothesis of the relationships and biogeography of Olmeca gen. nov. with other genera. http://zoobank.org/urn:lsid:zoobank.org:pub:F64CE801-7D82-4827-A5B9-0C0B41F58043